Universities and the public sphere : knowledge creation and state building in the era of globalization - Pusser, Brian (International studies in higher education., 2012)
In this volume, international contributors challenge prevalent views of the global marketplace to create a deeper understanding of higher education's role in knowledge creation and nation building.